IT Project Portfolio Optimization: A Risk Management Approach to Software Development Governance. - Bardhan, I. (Institutional Knowledge at Singapore Management University, 2010)
Little research has examined how to prioritize a portfolio of software projects. When project interdependencies are considered, the complexity of prioritizing even a small number of projects poses computational and evaluative challenges. We develop a prioritization approach to integrate real option analysis with a project portfolio optimization model. Our approach makes information technology (IT) portfolio risk management and valuation a meaningful tool for managers. Using real-world data, we implement the portfolio optimization model in a computationally feasible manner and demonstrate the superiority of our integrated optimization model. Our approach helps managers to make effective decisions, such as for investments in a service-oriented architecture, to enable flexible IT capabilities. When adaptability is paramount to success, managers can utilize our methods to inform themselves about the optimal timing of technology adoption decisions. Managers should recognize that IT investment decisions consist of many contingencies, so it is important to balance project-specific risks with the potential value derived across a multiperiod horizon. This permits us to make a contribution to the emerging discipline of software development governance in support of senior management decision making.